Kehidupan Sosial Anak Jalanan di Kota Makassar - Kamrin Kamrin (Departement of Mathematics Education, 2022)
The Social Life of street children in Makassar City is a description sourced from field research in Makassar City. Research on the lives of street children in the city of Makassar. This study used the interview method to compile the information needed. The type of research carried out is descriptive-qualitative research that aims to provide a description of the focus of this research. The results showed that the lives of street children are very poor and require systematic and targeted treatment.